A brief history of vaccines and anti-vax responses: the anti-vax movement - Kinch, Michael (Henry Stewart Talks, 2022)
Infectious diseases, Vaccine hesitancy, Variolation, Smallpox vaccine, Yellow journalism, Polio vaccine, DPT vaccine, Disease outbreaks, Brian Deer, Andrew Wakefield, HPV vaccine, COVID-19 vaccine, Modern vaccine development, Vaccines and politics